2009
DOI: 10.1073/pnas.0810738106
|View full text |Cite
|
Sign up to set email alerts
|

B2 RNA and Alu RNA repress transcription by disrupting contacts between RNA polymerase II and promoter DNA within assembled complexes

Abstract: Noncoding RNAs (ncRNAs) are now recognized as transregulators of eukaryotic transcription, a role once attributed exclusively to protein factors. Two ncRNAs in mammalian cells have been shown to repress general mRNA transcription by RNA polymerase II (Pol II) in response to heat shock: mouse B2 RNA and human Alu RNA. B2 and Alu RNAs bind directly and tightly to Pol II and co-occupy the promoters of repressed genes along with the polymerase. Here, we identified the molecular mechanism by which mouse B2 RNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
137
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 25 publications
5
137
1
Order By: Relevance
“…11 Within these inhibited complexes, B2 RNA disrupts the contacts between Pol II and the promoter DNA. 13 Consistent with this in vitro model for repression, cellbased experiments have co-localized Pol II and B2 RNA at the promoter of the repressed actin gene, specifically after heat shock in mouse cells. 12 We wondered what effect heat shock and B2 RNA would have on phosphorylation of the CTD of Pol II.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…11 Within these inhibited complexes, B2 RNA disrupts the contacts between Pol II and the promoter DNA. 13 Consistent with this in vitro model for repression, cellbased experiments have co-localized Pol II and B2 RNA at the promoter of the repressed actin gene, specifically after heat shock in mouse cells. 12 We wondered what effect heat shock and B2 RNA would have on phosphorylation of the CTD of Pol II.…”
mentioning
confidence: 72%
“…Previously, we had found that B2 RNA incorporates into complexes at the promoters of genes and represses transcription by keeping the polymerase from engaging promoter DNA. 13 Moreover, in heat-shocked cells we observed co-localization of B2 RNA and Pol II at the actin promoter. 12 Here we found that upon heat shock, Ser5 phosphorylation sharply decreases at the actin promoter, while the levels of TFIIH and total Pol II decrease to a much lower extent.…”
mentioning
confidence: 82%
“…Interestingly, it has been shown that SINEB2 RNAs are transcribed by RNA Pol III upon heat shock and repress transcription by disrupting the binding of RNA polymerase II to certain gene promoters [11,12]. In the case of the spliced antisense Uchl1 lncRNA, which contains SINEB2 and SINEB1 repeats, an effect on Uchl1 mRNA levels was not observed.…”
Section: Npgmentioning
confidence: 93%
“…These perispeckles are sites of active mRNA transcription that have been characterized as Btranscription factories^ (Brown et al 2008;Spector and Lamond 2011;Rieder et al 2012;Rieder et al 2014). The unique localization of HSPA6, but not HSPA1A, to perispeckles, suggests that HSPA6 may be associated with the recovery of transcription in human neuronal cells after inhibition by stressful stimuli (Allen et al 2004;Hieda et al 2005;Espinoza et al 2007;Yakovchuk et al 2009). Our on-going experiments indicate that localization of HSPA6 to perispeckles is disrupted by application of a transcriptional inhibitor during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%